Free-thiol Cys331 exposed during activation process is critical for native tetramer structure of cathepsin C (dipeptidyl peptidase I) - Horn, Martin; Baudys, Miroslav; Voburka, Zdenek; Kluh, Ivan; Vondrásek, Jirí; Mares, Michael (Protein science, 2002)
The mature bovine cathepsin C (CC) molecule is composed of four identical monomers, each proteolytically processed into three chains. Five intrachain disulfides and three nonpaired cysteine residues per monomer were identified. Beside catalytic Cys234 in the active site, free-thiol Cys331 and Cys424 were characterized. Cys424 can be classified as inaccessible buried residue. Selective modification of Cys331 results in dissociation of native CC tetramer into dimers. The 3D homology-based model of the CC catalytic core suggests that Cys331 becomes exposed as the activation peptide is removed during procathepsin C activation. The model further shows that exposed Cys331 is surrounded by a surface hydrophobic cluster, unique to CC, forming a dimer-dimer interaction interface. Substrate/inhibitor recognition of the active site in the CC dimer differs significantly from that in the native tetramer. Taken together, a mechanism is proposed that assumes that the CC tetramer formation results in a site-specific occlusion of endopeptidase-like active site cleft of each CC monomeric unit. Thus, tetramerization provides for the structural basis of the dipeptidyl peptidase activity of CC through a substrate access-limiting mechanism different from those found in homologous monomeric exopeptidases cathepsin H and B. In conclusion, the mechanism of tetramer formation as well as specific posttranslational processing segregates CC in the family of papain proteases.
Keywords: Molecular Sequence Data; Molecular Weight; disulfidy; sekvence aminokyselin; Cysteine; lysin; molekulová hmotnost; Disulfides; posttranslační úpravy proteinů; Chromatography, High Pressure Liquid; cystein; skot; vysokoúčinná kapalinová chromatografie; slezina; Peptide Fragments; Lysine; Enzyme Activation; Protein Conformation; Protein Processing, Post-Translational; kathepsin C; zvířata; Cathepsin C; Amino Acid Sequence; peptidové fragmenty; Cattle; aktivace enzymů; sbalování proteinů; molekulární sekvence - údaje; Spleen; Protein Folding; konformace proteinů; Animals